Aromatherapy in primary health care - Queiroz , Sacha Manoela Oliveira Paiva de Azevedo; Matos , Maria de Lourdes Medeiros de; Matos , Alcemar Antônio Lopes de; Mangiavacchi, Bianca Magnelli (Seven Editora, 2023)
The use of complementary health therapies, also called Natural or Alternative, has been highlighted in the developed countries of the West and in poor and developing countries, thanks to the stimulation made by the World Health Organization. In Brazil, especially, since 2018, public policies have undergone a process of expansion and integrative health practices such as Aromatherapy have been added to the Unified Health System (SUS). In this sense, the main objective of this study is to briefly report the history of aromatherapy, present its methodological trajectory, identify its functions in health care and defend its effectiveness in the field of Primary Health Care. This is a literature review, with a qualitative approach found in the Scielo and PubMED databases, available in Portuguese and English, without a specific temporal locus. The descriptors used in the search were: aromatherapy, primary health care, integrative and complementary health practices (PICs), and the Unified Health System (SUS). It is hoped that this research will contribute to the field of academic training and professional practice. DOI:https://doi.org/10.56238/sevened2023.004-004